Teachers’ Perception of Digital Literacy Skills as a Tool for 21st Century Teaching in Nigeria - Agarry, Rachael Ojima; Babalola, Moses Opeyemi; Jacob , Priscilla Ayooluwa (University of Dar es Salaam Library Journal, 2024)
The study examined teachers’ perception of digital literacy skills as a relevant tool for teaching in the 21st Century in Ilorin South Local Government Area of Kwara State. The descriptive research design was adopted. One research question and four research hypotheses were generated. The sampling technique was simple random sampling, selecting 200 teachers as respondents. The instrument used for data collection was a self-constructed questionnaire. Its reliability was determined using Cronbach’s alpha with 0.85 co-efficient. Descriptive and inferential statistical tools were employed in answering and testing the generated research question and the hypotheses respectively, using mean and standard deviation, independent t-test and ANOVA. The findings showed that teachers perceived digital literacy skills as a relevant tool for teaching in the 21st Century; there is a significant difference in the perception of teachers towards digital literacy skills for teaching in the 21st century based on gender and age while there is no significant difference in the perception of teachers towards digital literacy skills for teaching in the 21st Century based on educational qualification and years of teaching experience in Ilorin South. Recommendations were made that school managements should further encourage teachers’ digital literacy skills by organizing or sponsoring them to attend training on how to integrate e-learning tools into their classroom instructions; all age groups and both genders especially female teachers should be encouraged to acquire digital literacy skills among others.